Comparative evaluation of rivastigmine permeation from a transdermal system in the Franz cell using synthetic membranes and pig ear skin with in vivo-in vitro correlation - HEALY, ANNE (My University, 2016)
In the present study, in vitro permeation experiments in a Franz diffusion cell were performed using different synthetic polymeric membranes and pig ear skin to evaluate a rivastigmine (RV) transdermal drug delivery system. In vitro-in vivo correlations (IVIVC) were examined to determine the best model membrane. In vitro permeation studies across different synthetic membranes and skin were performed for the Exelon® Patch (which contains RV), and the results were compared. Deconvolution of bioavailability data using the Wagner–Nelson method enabled the fraction of RV absorbed to be determined and a point-to-point IVIVC to be established. The synthetic membrane, Strat-M™, showed a RV permeation profile similar to that obtained with pig ear skin (R2 = 0.920). Studies with Strat-M™ resulted in a good and linear IVIVC (R2 = 0.991) when compared with other synthetic membranes that showed R2 values less than 0.90. The R2 for pig ear skin was 0.982. Strat-M™ membrane was the only synthetic membrane that adequately simulated skin barrier performance and therefore it can be considered to be a suitable alternative to human or animal skin in evaluating transdermal drug transport, potentially reducing the number of studies requiring human or animal samples.
PUBLISHED
Export Date: 13 December 2016
Keywords: Franz diffusion cell; In vivo-in vitro correlation; Permeation; Point-to-point IVIVC; Rivastigmine; Strat-M™; Synthetic membrane; Transdermal drug delivery system; Franz diffusion cell; In vivo-in vitro correlation; Permeation; Point-to-point IVIVC; Rivastigmine; Strat-M™; Synthetic membrane; Transdermal drug delivery system